University alliances and firm exploratory innovation: Evidence from therapeutic product development. (September 2021) - Slavova, Kremena; Jong, Simcha
Abstract: This paper investigates the relationship between university alliances and firm exploratory innovation in the context of therapeutic product development. We build on organizational learning theory to elucidate that the use of university alliances is more positively associated with firm exploratory rather than exploitative innovation output. Moreover, we argue that the breadth of a firm's technological expertise strengthens the benefits of university alliances in the development of exploratory innovation output. Our empirical analysis is based on a panel dataset of 220 US therapeutic biotechnology firms from 2003 to 2010. Our findings support the contention that university alliances are differentially related to exploratory and exploitative innovation outcomes, and further indicate that firm technological breadth positively moderates the relationship between university alliances and firm exploratory innovation. Highlights: Benefits of university alliances contingent on type of firm innovation output. University alliances more beneficial for firm exploratory innovation output. This positive effect is stronger for firms with broader technological expertise. Results based on sample of 220 publicly traded therapeutic biotechnology firms.